Peranan Pembelajaran Inkuiri Terbimbing Terhadap Keterampilan Proses Sains dan Kemampuan Kognitif Peserta Didik - Amiruddin; Helmi; Muhammad Arsyad (Jurnal Penelitian Pendidikan IPA, 2025)
This experimental study aimed to analyze the science process skills and cognitive abilities of students taught through inquiry and hands-on learning. The independent variables were guided inquiry and hands-on learning, while the dependent variables were students' science process skills and cognitive abilities. The results of the descriptive analysis showed that the average KPS score in the guided inquiry group was 19.96 with a standard deviation of 2.01, while the direct learning group was 15.41 with a standard deviation of 4.04. For cognitive abilities, the average score in the guided inquiry group was 18.56 with a standard deviation of 4.18, while the direct learning group was 14.74 with a standard deviation of 3.40. These results indicate a difference in learning outcomes between the two groups, which can be used as a basis for further analysis. Based on the t-test results, there was a significant difference in cognitive abilities between the experimental and control classes (p = 0.001, where p < α = 0.05). Similarly, the difference in science process skills (SPS) was also significant (p = 0.000). These results indicate that guided inquiry learning plays a significant role in improving science process skills and provides a positive contribution to students' cognitive abilities compared to direct learning.